Interim Analysis and Feasibility of the Effects of Virtual Reality on Pain and Anxiety in Cancer Patients Undergoing Bone Marrow Biopsy - Wolfson, Hannah C; Mohacsi, Savannah; Pai, Jonathan; Xiong, Shigang; Nelson, Viva; Konganige, Shiran; Ghani, Umair; Pinski, Jacek K (Blood, 2024)
Introduction/Purpose We developed a protocol to test the hypothesis that the utility of Virtual Reality (VR) as a companion to bone marrow biopsy (BMBx) procedures will lessen patient experiences of pain and anxiety as indicated by patient-reported pain scores and anxiety surveys. The purpose of the present study was to examine the feasibility of this protocol. Methods We conducted a prospective, randomized study of 14 patients (of a planned total enrollment of 30 patients) undergoing BMBx. Patients were randomized 1:1 to the experimental arm (VR) or the control arm (standard of care). Pain surveys and the State Trait Anxiety Inventory (STAI) were completed before and after the BMBx procedure. Pain was rated on a scale from 0-10. The STAI scores were calculated as two sub-scores: State Anxiety Inventory (SAI) score and Trait Anxiety Inventory (TAI) score. Changes in pain and anxiety were calculated as the difference between recorded pain scores (∆Pain) and STAI sub-scores (∆SAI, ∆TAI) pre- minus post-BMBx. In R version 4.3.2, two sample t tests and Mann-Whitney U tests were used to compare changes in pain ratings and STAI sub-scores by experimental group. This was an interim analysis of 14 patients out of a planned 30 planned subjects to examine feasibility of the protocol. Results One patient did not complete any pain or STAI surveys and was excluded from analysis. Overall means (SD) for ∆Pain, ∆SAI, and ∆TAI were -0.92 (2.63), 2.46 (9.40), and 2.31 (3.82). Mean ∆Pain in the experimental group (n=8) and the control group (n=5) were -0.75 vs. -1.2, t test p=0.78, respectively. Mean ∆SAI in the experimental group and the control group were 2.875 vs. 1.8, t test p=0.84, respectively. Mean ∆TAI in the experimental group and the control group were 2.875 vs. 1.4, Mann Whitney U test p=0.46, respectively. Conclusion Differences were noted in pre- minus post- BMBx scores for pain and STAI sub-scores between the experimental group and the observational group. Although the differences in the means did not reach statistical significance due to the small number of subjects in the study, the results do support the feasibility of the protocol used in this pilot study to be expanded to a larger patient population and to a more diverse set of acutely painful procedures. No relevant conflicts of interest to declare.